PARTISIPASI MASYARAKAT DALAM MENGEMBANGKAN WISATA OLAHRAGA ARUNG JERAM DI DESA TIMBUKAR KECAMATAN SONDER KABUPATEN MINAHASA SULAWESI UTARA - Simanjuntak, Annabella E. (HOLISTIK, Journal of Social and Culture, 2024)
Community participation in the maintenance of natural resources owned is a large contribution and has the potential to become a tourist attraction. In addition, involving the community in the process and business of tourism development is very important, so that the community itself has a sense of responsibility to preserve the potential of natural resources owned. The participation of the community in maintaining natural and cultural resources owned is a large contribution and has the potential to become a tourist attraction. Sonder is a sub-district in Minahasa Regency, North Sulawesi. One of them is Timbukar Village where this village has an extreme sports tourism object, namely rafting. In several villages in Sonder District have several waterfall attractions that are very interesting to visit, one of which is the Kengkang Waterfall tourist attraction, the location of this tourist attraction can be seen before entering Timbukar Village. Sonder District has mountainous and hilly topographic characteristics, as well as air quality that can be said to be still very clean and cool. The form of community participation in the development of rafting tourism in Timbukar Village is contributing to being a tour guide, in collaboration with rafting operators, this is one form of community livelihood dominated by young people in Timbukar village. Keywords: community participation, sports tourism, rafting